Technology in anesthesiology: friend or foe? - Saasouh, Wael; Suchocki, Ewelina; Weeks, Matthew; McKelvey, George; Jaffar, Muhammad (Frontiers in Anesthesiology, 2024)
The field of medical technology has undergone significant advancements over the years, from the use of simple tools like knives and bones to complex devices like MRI machines and robotic surgical systems. These advancements have had a profound impact on the way we diagnose, treat, and prevent diseases, and have significantly improved the quality of life for millions of people around the world. As we move forward, it is important to reflect on the direction of medical technology and consider the potential risks and benefits of new advancements. We must also ensure that these technologies are accessible to all and that they are used ethically and responsibly. There is still much to be discovered and developed in the field of medical technology, and it is up to us to ensure that we are moving in a positive direction that benefits everyone.